2016
DOI: 10.1007/s10933-016-9887-1
|View full text |Cite
|
Sign up to set email alerts
|

Late quaternary hydrological changes at Tangra Yumco, Tibetan Plateau: a compound-specific isotope-based quantification of lake level changes

Abstract: Lake level fluctuations are important features in paleo-reconstructions that can be linked to past climate changes. Closed-basin lakes on the southcentral Tibetan Plateau record the balance between monsoonal precipitation and evaporative loss. To date, most studies provide only qualitative estimates of past hydrological changes. For the first time, we applied hydrogen isotopes (dD) of aquatic and terrestrial nalkanes to quantify lake volume changes of Tangra Yumco and compared values to newly calculated lake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Tangra Yumco sediments have already been investigated for palaeoecological and palaeoclimatic purposes in the recent years (Long et al ., ; Rades et al ., ; Miehe et al ., ; Ahlborn et al , , ; Akita et al ., ; Günther et al ., ; Henkel et al ., ). Ahlborn et al () reconstructed the lake level history based on OSL dating (Fig.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tangra Yumco sediments have already been investigated for palaeoecological and palaeoclimatic purposes in the recent years (Long et al ., ; Rades et al ., ; Miehe et al ., ; Ahlborn et al , , ; Akita et al ., ; Günther et al ., ; Henkel et al ., ). Ahlborn et al () reconstructed the lake level history based on OSL dating (Fig.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…In the last decade, several studies of lacustrine sediments from the Tibetan Plateau identified significant lake level changes during the Late Quaternary that are related to monsoon and westerlies variability (Mischke and Zhang, ; Kasper et al ., ; Günther et al , , , ; Mishra et al ., ; Ahlborn et al , ; Henkel et al , ). Due to the role of this area as origin of many large rivers of south‐eastern Asia, the climate variations in this area force environmental, social and economic consequences for millions of people and their better understanding is urgently needed to offer indications of future scenarios.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…With a total area of 41 800 km 2 , it has been estimated that more than 1000 lakes distributed on TP are larger than 1 km 2 (Ma et al ., ; Witt et al ., ). Glacier melt has greatly supported the development of many inland TP lakes because these are fed by glaciers located in their catchments (Yao et al ., ; Zhu et al ., ; Günther et al ., ). Conversely, many other climatic factors such as increased precipitation and decreased evaporation from lake surfaces may have contributed significantly to the expansion of lakes which are not fed by glaciers in their catchment (Liu et al ., ).…”
Section: Responses Of Hydrosphere To Climate Change Over Tpmentioning
confidence: 97%
“…An average Lake Surface Temperature of 9 • C was selected for the calculations. A more detailed explanation of the calculation is provided in Günther et al (2016).…”
Section: Analysis Of Sedimentary N-alkanesmentioning
confidence: 99%